THERMODYNAMIC POTENTIAL OF THE BOSE GAS - Taylanov, Nizom; Urinov, Sunat; Narimanov, Bahodir; Urazov, Abduxoliq (Физико-технологического образование, 2021)
In this paper we investigated and the dependence of the chemical potential on temperature in the vicinity of and below the transition Bose condensation. It should be noted that below the Bose condensation chemical potential has microscopic order. It was shown that below bose condensation point chemical potential is inversely proportional to the number of condensate particles.